Effect of Gynura procumbens (Sambung Nyawa) on Sheep Performance, Health Status, and Methane Emission: Efek Gynura procumbens (Sambung Nyawa) pada Performa, Status Kesehatan dan Emisi Gas Metana pada Domba - Yusfani, Ade Dini; Yuniartika; Yunizar, Mahira Revida; Rahmah, Elia; Purba, Prans; Sunardi; Kumalasari, Nur Rochmah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
Gynura procumbens (Sambung nyawa) has been widely used as a herbal medicine since it is rich in bioactive compounds. Moreover, Gynura procumbens also has become a potential plant that control parasitic nematode infection. The research aimed to investigate the effect of G. procumbens on sheep performance, health status, and methane production. A total of twelve six-month-old lambs (ABW 11.27 ± 2.19 kg) were categorized based on live weight and fed one of feed treatments: wild grasses (40%) and concentrate (60%) (control/P0), P0 + 5% G. procumbens (P1), and P0 + 10% G. procumbens (P2). Feed intake, parasitic infection, and physiological status were measured weekly. G. procumbens at 5% level showed normal respiration rate, but the respiration and heart rates of lambs were abnormal. The 10% G. procumbens increased daily weight gain. G. procumbens addition up to 10% reduced the number of Strongyloides on feces and enteric methane emissions compare to control. It concluded that 5% G. procumbens can be used as an anthelmintic forage by improving health status, performance, and reducing methane emissions of sheep. Key words: Gynura procumbens, herb medicine, nematodes infection, parasite population, sheep performance